SPE Annual Technical Conference and Exhibition 2012
DOI: 10.2118/159550-ms
|View full text |Cite
|
Sign up to set email alerts
|

Closed-loop Feedback Control in Intelligent Wells: Application to a Heterogeneous, Thin Oil-Rim Reservoir in the North Sea

Abstract: Important challenges remain in the development of optimized control strategies for intelligent wells, particularly with respect to incorporating the impact of reservoir uncertainty. Most optimization methods are model-based and are effective only if the model or ensemble of models used in the optimization capture all possible reservoir behaviors at the individual well and completion level. This is rarely the case. Moreover, reservoir models are rarely predictive at the spatial and temporal scales required to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…To keep the problem tractable, we employ a simple box reservoir model, characterized by 50 × 50 × 167 simulation cells. Each cell has an approximate dimension of 20 m × 20 m × 3 m. The choice of cell area dimension of 20 m × 20 m was arbitrary, but finer than the cell dimensions of 50 m × 50 m and 100 m × 100 m typically used to simulate realistic reservoirs in practice (Lawal et al 2016(Lawal et al , 2017Dilib et al 2015;Uwaga and Lawal 2006;Kabir et al 2004). However, prior grid sensitivity tests suggested that a 3 m layer thickness was adequate to achieve computational efficiency without significant numerical artefacts for this specific model.…”
Section: Numerical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…To keep the problem tractable, we employ a simple box reservoir model, characterized by 50 × 50 × 167 simulation cells. Each cell has an approximate dimension of 20 m × 20 m × 3 m. The choice of cell area dimension of 20 m × 20 m was arbitrary, but finer than the cell dimensions of 50 m × 50 m and 100 m × 100 m typically used to simulate realistic reservoirs in practice (Lawal et al 2016(Lawal et al , 2017Dilib et al 2015;Uwaga and Lawal 2006;Kabir et al 2004). However, prior grid sensitivity tests suggested that a 3 m layer thickness was adequate to achieve computational efficiency without significant numerical artefacts for this specific model.…”
Section: Numerical Modelmentioning
confidence: 99%
“…The early and sustained production of these unwanted associated fluids increases the operating expenses related to handling gas and water produced per unit volume of oil recovered, hence eroding project value. Because coning rates are usually below economic thresholds, the strategy of limiting oil offtake below gas and water coning rates has not recorded significant success in practice (Balogun et al 2015;Dilib et al 2015;Yeoh 2014;Lawal et al 2010;Kromah and Dawe 2008;Uwaga and Lawal 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doublet et al (2009) formulated a constrained optimization problem as an augmented Lagrangian saddle point problem. Dilib et al (2012) optimized a closed-loop strategy using a base case model, and then tested against unexpected reservoir behavior by adjusting a number of uncertain parameters in the model. They found that closedloop feedback control yields positive gains in NPV for the majority of reservoir behaviors investigated, and higher gains than the open-loop strategy since closed-loop control can also yield positive gains in NPV even when the reservoir does not behave as expected.…”
Section: Intelligent Well Production Optimizationmentioning
confidence: 99%
“…The use of control policies [1,[17][18][19] has proven to be an effective technique to address the conservative nature of robust optimization solutions in reservoir management problems. These control policies are designed to map observed data to optimal well settings.…”
Section: Introductionmentioning
confidence: 99%